Politics of Islamic Education at Pesantren Darush Sholihin 2: Policy Study and Implementation in Local Context - Irfan Tamwifi; Eliyyil Akbar; Mohd Nazri Abdul Rahman (LP. Ma'arif Janggan Magetan, 2024)
This study investigates how Islamic education policies at Darush Sholihin 2 Islamic Boarding School are shaped by political, social, and cultural forces in a local context. While national regulations set standardized curricular and accreditation requirements, pesantren traditions and community expectations drive contextual adaptation. A qualitative case-study approach was used. Data were collected via semi-structured interviews with the kyai, bu nyai, teachers, and local education officials; non-participant observations of classes and dormitory life; and analysis of policy documents. Thematic coding and triangulation enhanced validity. Darush Sholihin 2 formally implements Ministry of Religious Affairs standards yet embeds regional wisdom—local language, artisanal crafts, and indigenous moral frameworks—into its pedagogy. Three key factors influence this implementation: (1) the kyai and bu nyai’s leadership in negotiating curriculum adaptations; (2) supportive yet flexible local government oversight; and (3) pressures to modernize through e-learning and standardized assessments, which prompt hybrid educational strategies. Findings reveal that policy enactment at Darush Sholihin 2 emerges from continuous negotiation among state authorities, religious leaders, and globalization pressures, rather than top-down imposition. This negotiated model strengthens cultural relevance, stakeholder engagement, and institutional resilience. For policymakers and pesantren administrators, granting structured flexibility enables innovation without compromising tradition.